Absorption/regeneration performance evaluation of methanol based magnetic nanoabsorbent for industrial CO2 capture applications. Issue 54 (December 2021) - Park, Jong Ha; Lee, Jae Won; Kim, Seonggon; Xu, Ronghuan; Kang, Yong Tae
Graphical abstract: Highlights: Magnetite is successfully coated with ascorbic acid and their properties are measured. 23.3 % of CO2 absorption is obtained by the effect of magnetic fields. Mechanisms of CO2 capture process with magnetic fields is closely discussed. Energy consumption analysis shows the merit of this study for industrial application. Abstract: In the present study, surface modification of Fe3 O4 particles with ascorbic acid (AA-Fe3 O4 ) is carried out to enhance the absorption and regeneration performances of Fe3 O4 nanoabsorbents with magnetic fields. The surface modified AA-Fe3 O4 particles compensate for the defects of commercial magnetic nanoparticles by enhanced hydrophilicity and increased surface area. Methanol, which is widely used as a conventional industrial physical absorbent of CO2 capture, is used as a base fluid; however, the absorption process must be operated at low temperature for high absorption performance. In addition, a substantial amount of energy input is required to reach the regeneration operating temperature. Manufactured AA-Fe3 O4 is analyzed using various analysis methods to assess absorption characteristics. Furthermore, a property analysis of 0.005 vol% AA-Fe3 O4 dispersed in methanol shows that a high dispersion stability is obtained compared to 0.005 vol% commercial Fe3 O4 dispersed in methanol. An evaluation on the performance of AA-Fe3 O4 at 25 °C in the presence of external rotating magnetic fields shows an enhancement of 23.3 % in absorption. According to the specific energy consumption analysis, it is concluded that AA-Fe3 O4 /methanol nanoabsorbents will be beneficial for industrial applications in efficient energy savings for CO2 capture.